Sarah Bernhardt : The Art Within the Legend - Taranow, Gerda (Book collections on Project MUSE., 1972)
Through a study of the actress' films, records and writings, Gerda Taranow reconstructs the rigorously developed artistry that lay behind the superb performances. Analyzing each histrionic element and discussing repertoire she shows how Bernhardt adapted the techniques learned at the Conservatoire and in the theatre to her own particular strengths and limitations.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.